Efektivitas Penggunaan Media Pembelajaran Visual pada Mata Pelajaran Matematika Terhadap Prestasi Belajar Siswa - Anwar Anwar; Wa Ode Sarfia Ode Rahimu (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The purpose of this research was to see the effectiveness of learning with visual learning media using a digital projector on student achievement at SMP Negeri 1 Tomia. This research used quantitative approach with quasi experiement. Population of this research was all student of eighth grade a SMP Negeri 1 Tomia that consisted of 3 parallel classes. Because the population hand homogeneous learning achievement, the sample was taken from two classes, namely class VIIIA and class VIIIB. Data collection technique in research used test. The results of research were the significant value was 0.001, the N-gain value obtained a difference in the average value of students’ mathematics learning achievement of the experimental class by 65.07 and the control class by 44.46. Then the effectiveness criterion was based on the gain score obtauned by the percentage of the experimental class of 65.07% which was categorized as quite effective because it was between 56% and 75%, so that Ho was rejected and H1 was accedted based on the hypothesis acceptance criteria. This meant that the application of visual learning media using a digital projector was quite effective on the mathematics learning achievement of grade VIII students of SMP Negeri 1 Tomia on the subject of number patterns.